2021
DOI: 10.1111/gcb.15647
|View full text |Cite
|
Sign up to set email alerts
|

Parental whole life cycle exposure modulates progeny responses to ocean acidification in slipper limpets

Abstract: Multigenerational exposure is needed to assess the evolutionary potential of organisms in the rapidly changing seascape. Here, we investigate if there is a transgenerational effect of ocean acidification exposure on a calyptraeid gastropod such that long‐term exposure elevates offspring resilience. Larvae from wild type Crepidula onyx adults were reared from hatching until sexual maturity for over 36 months under three pH conditions (pH 7.3, 7.7, and 8.0). While the survivorship, growth, and respiration rate o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 67 publications
(92 reference statements)
0
13
0
Order By: Relevance
“…One study found that OA can increase fecundity, and another found that low pH increased reproductive output, but at the cost of body size and shell integrity (Fitzer et al, 2012b;Engström-Öst et al, 2014). In molluscs, OA exposure during breeding reduced bivalve brood size (Wippel, 2017;Maboloc and Chan, 2021), while a previous OA exposure resulted in increased brood size but no effect to overall larval production (Spencer et al, 2020). Instances where reproductive output increases may be a short-term stress response or may indicate adaptive potential to pH change (Engström-Öst et al, 2014).…”
Section: Fecundity and Reproductive Outputmentioning
confidence: 99%
“…One study found that OA can increase fecundity, and another found that low pH increased reproductive output, but at the cost of body size and shell integrity (Fitzer et al, 2012b;Engström-Öst et al, 2014). In molluscs, OA exposure during breeding reduced bivalve brood size (Wippel, 2017;Maboloc and Chan, 2021), while a previous OA exposure resulted in increased brood size but no effect to overall larval production (Spencer et al, 2020). Instances where reproductive output increases may be a short-term stress response or may indicate adaptive potential to pH change (Engström-Öst et al, 2014).…”
Section: Fecundity and Reproductive Outputmentioning
confidence: 99%
“…It could be selection, through selective mortality of females poorly adapted to low pH, or transgenerational plasticity [22]. Transgenerational and selective breeding experiments suggest that many species have the capacity to evolutionarily adapt to ocean acidification via natural selection [26,[53][54][55][56]. In the case of snow crabs, the mortality over the course of the experiment did not vary much between the treatments which makes this a less likely, though still possible, mechanism [57].…”
Section: Discussionmentioning
confidence: 99%
“…These studies suggest that parents can transmit information that may benefit offspring survival. Through this transgenerational plasticity (also known as transgenerational acclimation [16][17][18]), parents may provide offspring with increased tolerance to environmental perturbations, such as contaminants [1][2][3][4][5], food shortages [19,20], carbon dioxide [21][22][23][24], hypoxia [25], salinity [26][27][28], and temperature [20,[29][30][31][32][33][34][35]. Studies have tended to focus on maternal transgenerational plasticity, or have exposed both parents to the environmental perturbation, making it impossible to disentangle the relative roles of mothers and fathers in altering offspring phenotype [36,37].…”
Section: Introductionmentioning
confidence: 99%